Polyimide resin sizing method of high-thermal-conductivity mesophase pitch-based carbon fiber

The polyimide resin sizing method, which involves multi-stage processing and process optimization, solves the problem of poor interfacial bonding of high thermal conductivity mesophase pitch-based carbon fibers, enabling high-performance applications of composite materials and improving the bonding strength and thermal conductivity between the fiber and the matrix.

CN120925314APending Publication Date: 2025-11-11HUNAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511026518.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In the prior art, the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers has failed to effectively treat the fiber materials, resulting in poor interfacial bonding and affecting the practical application performance of the composite materials.

Method used

A multi-stage treatment method is adopted, including the pretreatment of fiber materials, the formulation of polyimide resin and the optimization of sizing process, combined with spraying and impregnation methods, plasma treatment to enhance surface activity, control process parameters to ensure uniform penetration and curing, and optimize the interfacial bonding between fiber and resin.

Benefits of technology

It significantly improves the interfacial bonding force between the fiber and the matrix and the mechanical properties of the composite material, enhances thermal conductivity and thermal stability, solves the performance fluctuation problem caused by differences in a single process parameter, and realizes the production of high-performance carbon fiber composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120925314A_ABST
    Figure CN120925314A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite material production and processing, and discloses a high-thermal-conductivity mesophase pitch-based carbon fiber polyimide resin sizing method which comprises the following steps: S1, carrying out early-stage pretreatment on the surface of a fiber material; s2, preparing polyimide resin sizing liquid; s3, a sizing process is carried out on the surface of the fiber material; s4, performing multi-stage curing treatment on the fiber material; s5, carrying out influence analysis on the process parameters; according to the method, by selecting a proper sizing method and optimizing technological parameters, good interface bonding between fibers and a matrix can be achieved, the mechanical property and the heat stability of the composite material are improved, meanwhile, the interface bonding force and the heat-conducting property of the carbon fiber composite material can be remarkably improved, and the performance of the carbon fiber composite material is improved. And uniform coating and complete curing of the resin are ensured, so that the production target of the high-performance carbon fiber composite material is achieved, and the performance of the prepared carbon fiber composite material can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material production and processing technology, specifically to a method for sizing polyimide resin onto high thermal conductivity mesophase pitch-based carbon fibers. Background Technology

[0002] High thermal conductivity mesophase pitch-based carbon fiber is a material with excellent physical properties, especially in terms of thermal conductivity and lightweight. To further enhance its application performance in composite materials, sizing is often used to improve the interfacial bonding between the fiber and the matrix. Polyimide resin, as a high-performance polymer, is often used as a sizing agent due to its excellent heat resistance, mechanical properties, and chemical stability. By coating the surface of high thermal conductivity mesophase pitch-based carbon fiber with polyimide resin, the bonding strength between the fiber and the matrix can be enhanced, thereby improving the overall mechanical properties of the composite material. High thermal conductivity mesophase pitch-based carbon fiber is easily damaged during processing, and sizing can play a protective role, reducing the risk of breakage. After sizing, high thermal conductivity mesophase pitch-based carbon fiber is easier to disperse and uniformly distribute in the matrix, which helps to improve the molding quality and consistency of the composite material. Current sizing methods for polyimide resin sizing suffer from several drawbacks. First, the resin sizing solution is not effectively treated before sizing, resulting in suboptimal interfacial bonding between the sizing solution and the carbon fiber material. Second, the lack of effective curing after sizing prevents the resin sizing solution from effectively fusing and curing with the carbon fiber material, thus impacting the subsequent practical application performance of the composite material. Summary of the Invention

[0003] To address the shortcomings of existing technologies, this invention provides a method for sizing polyimide resin onto high thermal conductivity mesophase pitch-based carbon fibers. This method solves the problems of current sizing methods where the resin sizing solution is not effectively treated before sizing, resulting in unsatisfactory interfacial bonding between the sizing solution and the carbon fiber material. Furthermore, the lack of effective curing after sizing prevents the resin sizing solution from effectively fusing and curing with the carbon fiber material, thus affecting the subsequent practical application performance of the composite material.

[0004] To achieve the above objectives, the present invention provides the following technical solution: a method for sizing high thermal conductivity mesophase pitch-based carbon fibers with polyimide resin, comprising the following steps: Step S1, Pre-treatment of the fiber material surface; Step S2: Prepare the polyimide resin sizing solution; Step S3: Apply a sizing process to the surface of the fiber material; Step S4: Multi-stage curing treatment of fiber materials; Step S5: Perform an impact analysis on the process parameters; Step S6: Post-performance testing of fiber materials.

[0005] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers of the present invention, step S1 involves pretreating the high thermal conductivity mesophase pitch-based carbon fibers to enhance the wettability of the fiber material surface and its interfacial bonding force with the resin sizing liquid. Before treating the fiber material, it is necessary to determine the fiber diameter and bundle number of the fiber material. The specific pretreatment methods include the following steps: S101, Cleaning treatment; S102, drying treatment; S103, surface activated; In step S101, the aim is to remove contaminants adsorbed on the surface of the carbon fiber material, improve the cleanliness of the carbon fiber material surface, and facilitate better subsequent sizing. In the specific cleaning process, organic solvents are used in combination with ultrasonic cleaning equipment to perform ultrasonic cleaning treatment on the mesophase pitch-based carbon fiber material to remove impurities on the surface of the carbon fiber material. During the ultrasonic cleaning process, it is necessary to ensure that the structural integrity of the carbon fiber is not affected. In step S102, the aim is to remove the water stains remaining during the cleaning process of the carbon fiber material. In the specific drying process, the cleaned carbon fiber material is placed in a vacuum oven at a drying temperature of 60-80°C for 8-12 hours until the fiber material is completely dry and there is no solvent or moisture residue. In step S103, the surface of the carbon fiber material is activated to improve its surface activity. Specifically, the surface of the carbon fiber material is activated by a plasma treatment device to increase the surface roughness and active sites. The power of the plasma treatment device is 200-400 watts, and the treatment time is 4-10 minutes.

[0006] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers of the present invention, step S2 specifically includes preparing a polyimide precursor solution and adding other functional fillers therein to optimize the sizing performance, specifically including the following steps: S201, dissolving resin; S202, with added thermally conductive filler; S203, dilution adjustment; In step S201, specifically, polyimide powder is taken, an appropriate amount of solvent is added, and it is fully dissolved until a stable solution with a solid content of 10-20% is obtained. During the dissolution process, mechanical stirring is used to assist the dissolution until a uniform and transparent liquid solution is formed. In step S202, thermal conductivity is enhanced by adding thermally conductive filler. The amount of thermally conductive filler added is controlled at 5-15%. The thermally conductive filler is uniformly dispersed in the matrix by ball milling. In step S203, the amount of solvent is adjusted according to the required viscosity until the viscosity is adjusted to 2000-5000 mPa•s at 25°C to meet the coating requirements. Excessive viscosity can lead to uneven resin adhesion during coating, while excessively low viscosity can affect the stability of the coating. Therefore, it is necessary to flexibly control the viscosity to ensure fiber wettability and coating uniformity. In the process of controlling viscosity, the viscosity is measured by a rotational viscometer. When the viscosity is insufficient, i.e., viscosity <2000 mPa•s, the resin ratio can be increased. When the viscosity is too high, i.e., viscosity >5000 mPa•s, solvent can be added for dilution.

[0007] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fiber of the present invention, step S3 is to uniformly coat and deposit the prepared polyimide resin sizing liquid onto the surface of the carbon fiber material. Specifically, a superimposed sizing process combining spraying and impregnation is adopted to achieve sizing. The spraying equipment involved in the spraying method and the sizing tank involved in the impregnation method are integrated and connected to form a single-channel sizing process line. During the sizing process, the carbon fiber material is moved by a traction device. As the carbon fiber material passes through the spraying equipment, the sizing liquid is atomized into fine droplets and evenly sprayed onto the surface of the carbon fiber material using an atomizing device. During the spraying process, it is necessary to control the spraying pressure and spraying spacing. The spraying pressure is controlled at 0.2-0.5MPa, and the spraying spacing refers to the distance between the nozzle and the carbon fiber material. The spraying spacing is 10-20cm to achieve sizing by spraying. After the carbon fiber material is fully sprayed by the spraying equipment, the traction equipment pulls the carbon fiber material to continue moving to the sizing tank. During the process of the traction equipment pulling the carbon fiber material, the sprayed carbon fiber material is slightly shaken, so that the sizing liquid adsorbed by the spraying can fully penetrate into the carbon fiber material. Meanwhile, under the traction of the traction equipment, the carbon fiber material after spraying will be slowly pulled to the sizing tank and stably passed through the sizing tank to achieve sizing. During the sizing process, it is necessary to control the moving speed between the carbon fiber material and the sizing tank, and at the same time control the residence time of the carbon fiber material in the sizing tank. The moving speed is 1-3m / min and the residence time is 10-20 seconds.

[0008] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fiber of the present invention, in step S3, after the carbon fiber material passes through the sizing tank, the moisture content of the sizing film layer of the carbon fiber material needs to be precisely controlled by the extrusion roller. The moisture content needs to be controlled between 20-40% to ensure that the carbon fiber material is completely impregnated and there are no air bubbles.

[0009] As a preferred embodiment of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers of the present invention, step S4, which involves curing treatment to fully convert the polyimide resin into a stable polymer structure, specifically includes the following curing treatment steps: S401, preliminary drying treatment; S402, multi-step stepped curing treatment; In step S401, the carbon fiber material after sizing is transferred to a hot air oven for preliminary drying. The drying temperature of the hot air oven is controlled at 80-100℃ and the drying time is set to 5-10 minutes to allow some of the solvent inside the carbon fiber material to evaporate, while avoiding solvent loss or thinning of the coating layer due to solvent vaporization. In step S402, the multi-step stepped curing process includes two stages: a first curing stage and a second curing stage. The time and temperature of the two curing stages need to be adjusted accordingly based on the selected steps. In the first curing stage: the carbon fiber material after preliminary drying is placed in a constant temperature oven at 120-150℃ for 2-3 hours to complete the subsequent oligomerization reaction, form a partially cross-linked structure, and avoid matrix structure defects and unevenness. In the second curing stage: the carbon fiber material cured in the first fixing stage is placed in a high-temperature oven at 280-300℃ for 1-2 hours to complete the high-temperature cross-linking polymerization of the matrix, form a three-dimensional network structure, and improve the thermal stability of the material. In the initial drying stage, the first curing stage, and the second curing stage of carbon fiber materials, at the end of each stage, the carbon fiber materials need to be allowed to cool naturally to room temperature to ensure the curing effect of each stage. In the second curing stage, the temperature needs to be kept stable to prevent excessively high local temperatures from causing degradation or oxidation reactions.

[0010] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fiber of the present invention, in step S4, after the carbon fiber material is processed and cured, the surface of the carbon fiber material needs to be optimized. The specific optimization methods include surface trimming and annealing. During surface finishing, an electrostatic elimination device is used to reduce electrostatic adsorption and prevent fiber aggregation caused by static electricity. At the same time, a light roller pressing method is used to improve fiber bundle properties and ensure uniform and gentle contact between fibers. During annealing, the material is treated at 250°C for 1 hour in a nitrogen-protected environment to release the internal stress generated during curing and increase the stability of the interfacial bonding. After annealing, the fiber material is cooled to room temperature.

[0011] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fiber of the present invention, step S5 involves the sizing and curing process of the fiber material, wherein the process parameters involved include impregnation time, curing temperature, fiber diameter and number of bundles. The optimization of impregnation time aims to ensure uniform penetration of the sizing liquid without bubbles, and the optimization of curing temperature aims to maximize the degree of resin crosslinking and interfacial bonding. The impregnation time and curing temperature need to be adjusted according to the fiber diameter and the number of bundles. The optimal parameter combination is determined by adjustment. Specifically, this includes analyzing the relationship between impregnation time and fiber diameter and the number of bundles, and analyzing the relationship between curing temperature and fiber diameter and the number of bundles. When analyzing the relationship between impregnation time and fiber diameter and bundle number, the impregnation time directly affects the penetration depth and adsorption uniformity of the sizing solution on the carbon fiber surface. Fiber diameter and bundle number affect the impregnation time through the following mechanisms, where fiber diameter is divided into fine fibers and coarse fibers, and bundle number is divided into high bundle number and low bundle number: Fine fibers have a large specific surface area, so the sizing solution is absorbed faster, but the pores are smaller and the permeation resistance is greater. Coarse fibers have a small specific surface area, so the absorption is slower, but the permeation resistance is smaller. Therefore, the impregnation time is negatively correlated with the fiber diameter. As the fiber diameter increases, the impregnation time decreases. A high bundle number means that more monofilaments are tightly packed, with the inner fibers being wrapped by the outer fibers. The sizing solution needs a longer time to penetrate into the bundle. A low bundle number means that the fibers are dispersed and penetration is easier. Therefore, the impregnation time is positively correlated with the bundle number. As the bundle number increases, the impregnation time is extended. When analyzing the relationship between curing temperature and fiber diameter and bundle number, the curing temperature affects the crosslinking reaction rate and extent of polyimide resin. Fiber parameters influence temperature selection through the following mechanisms: Fine fibers have a large specific surface area, short resin diffusion paths, and fast reaction rates, requiring lower temperatures to avoid over-curing. Coarse fibers have long diffusion paths and slow reaction rates, requiring appropriate temperature increases to promote cross-linking. Therefore, curing temperature is negatively correlated with fiber diameter; as fiber diameter increases, temperature decreases. High-bundle-count fiber bundles have more internal voids, requiring a longer resin diffusion time and necessitating higher temperatures to accelerate the reaction. Low-bundle-count fibers are more dispersed, resulting in a more uniform reaction and allowing for lower temperatures. Therefore, curing temperature is positively correlated with the bundle number; as the bundle number increases, the temperature rises.

[0012] As a preferred technical solution for the polyimide resin sizing method of high thermal conductivity mesophase pitch-based carbon fibers of the present invention, in step S5, the impregnation time and curing temperature are optimized, with fiber diameter and bundle number as control factors and impregnation time and curing temperature as response variables. During the optimization of impregnation time, the fiber diameter was 3μm, the number of bundles was 1K, and other process parameters were kept constant. The impregnation time was adjusted in 1s increments within the range of 5-10s. The amount of sizing was measured. If the amount of sizing was less than the target amount of sizing, the impregnation time needed to be extended. If the amount of sizing was greater than the target amount of sizing or air bubbles appeared, the impregnation time needed to be shortened in order to determine the optimal impregnation time. During the curing temperature optimization process, the first stage temperature was 120-150℃, and the second stage temperature was 280-300℃. The temperature was adjusted in increments of 10℃ within the temperature range, and the performance after curing was tested. The higher the curing temperature, the better the degree of crosslinking, the higher the shear strength, and the stronger the interfacial bonding force, so as to determine the final optimal first stage temperature and second stage temperature.

[0013] As a preferred technical solution of the polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers of the present invention, step S6, the performance testing of the fiber material, is a comprehensive performance evaluation of the sized fiber material to ensure that the fiber material can meet the actual production requirements. The specific performance testing process includes the following testing steps: S601, thermal conductivity test; S602, Shear performance test; In step S601, the thermal conductivity test is performed by measuring the axial thermal conductivity of the fiber material using the laser flare method. The standard target value should be ≥10W / (m•K) to verify the thermal conductivity required for fiber reinforcement. During the thermal conductivity test, it is necessary to repeat the measurement multiple times in a standard high thermal conductivity environment to ensure the accuracy and reliability of the data; In step S602, the shear performance test is to test the interfacial shear strength of the fiber material. The interfacial bonding force between polyimide and carbon fiber is evaluated by using a single fiber pull-out test, and the peel strength value needs to be paid attention to. Typically, a peel strength value greater than 40 MPa is expected to be required to verify the overall mechanical properties of the material after matrix reinforcement.

[0014] Compared with the prior art, the present invention provides a method for sizing polyimide resin onto high thermal conductivity mesophase pitch-based carbon fibers, which has the following beneficial effects: 1. This polyimide resin sizing method can significantly improve the application performance of high thermal conductivity mesophase pitch-based carbon fibers in composite materials. By selecting a suitable sizing method and optimizing process parameters, a good interfacial bond between the fiber and the matrix can be achieved, improving the mechanical properties and thermal stability of the composite material. At the same time, it can significantly improve the interfacial bonding force and thermal conductivity of carbon fiber composite materials, ensuring uniform resin coating and complete curing, thereby achieving the production goal of high-performance carbon fiber composite materials and greatly improving the performance of the prepared carbon fiber composite materials. Furthermore, by analyzing the correlation between impregnation time, curing temperature, fiber diameter, and number of bundles, the optimal parameter combination was determined, solving the performance fluctuation problem caused by fiber parameter differences in a single process. This provides a guarantee for the stability of the third bonding process, achieving precise matching between sizing process parameters and fiber characteristics, solving the problems of uneven penetration and residual bubbles, and significantly improving the comprehensive performance of the composite high thermal conductivity mesophase pitch-based carbon fiber.

[0015] 2. In the sizing treatment of thermally conductive mesophase pitch-based carbon fibers, this invention employs a combination of spraying and impregnation. Spraying addresses the surface coverage issue, while impregnation addresses the internal penetration issue. During the spraying stage, the high specific surface area of ​​the atomized droplets allows for rapid coverage of the outer fibers of the fiber bundle, and spraying can complete the initial wetting of the outer fibers in a short time, thus enabling rapid pre-wetting and optimizing the surface condition. During the impregnation stage, the continuous movement of the fiber material in the sizing tank allows the sizing liquid to fully contact the monofilaments inside the fiber bundle, achieving deep penetration and enhancing overall uniformity. Combined with the pre-wetting effect of spraying, the advantages of the impregnation stage are further amplified. Through the synergistic effect of pre-wetting, deep penetration, and precise humidity control, the invention significantly outperforms traditional single spraying or impregnation methods in core indicators such as uniformity, bubble control, thermal conductivity, and interfacial bonding, thereby improving the actual sizing bonding effect. Attached Figure Description

[0016] Figure 1 This is a detailed process flow diagram of the sizing method of the present invention. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.

[0018] In the description of this invention, it should be noted that when an element is referred to as being "fixed to" or "set on" another element, it can be directly on or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to or indirectly connected to the other element.

[0019] In the description of this invention, it should be noted that the terms "center," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product of this invention is in use. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third," etc., are used only to distinguish descriptions and should not be construed as indicating or implying relative importance. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified. "Several" means one or more, unless otherwise explicitly specified.

[0020] In the description of this invention, it should also be noted that, unless otherwise explicitly specified and limited, the terms "set," "install," "connect," and "link" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0021] Example: Please refer to Figure 1 The present invention provides the following technical solution: a method for sizing polyimide resin onto high thermal conductivity mesophase pitch-based carbon fibers, comprising the following steps: Step S1, Pre-treatment of the fiber material surface; Step S2: Prepare the polyimide resin sizing solution; Step S3: Apply a sizing process to the surface of the fiber material; Step S4: Multi-stage curing treatment of fiber materials; Step S5: Perform an impact analysis on the process parameters; Step S6: Post-performance testing of fiber materials.

[0022] Step S1 involves pretreating the high thermal conductivity mesophase pitch-based carbon fiber to enhance the wettability of the fiber surface and its interfacial bonding with the resin slurry. Before pretreating the fiber material, it is necessary to determine the fiber diameter and bundle number. The specific pretreating methods include the following steps: S101, Cleaning treatment; S102, drying treatment; S103, surface activated; In step S101, the aim is to remove contaminants adsorbed on the surface of the carbon fiber material, improve the cleanliness of the carbon fiber material surface, and facilitate better subsequent sizing. In the specific cleaning process, an organic solvent is used, and the organic solvent is selected as a mixture of acetone and ethanol. The mixing ratio of the mixture is 1:1, and the concentration of the acetone and ethanol cleaning solution mixture is controlled at 12%. The mesophase pitch-based carbon fiber material is ultrasonically cleaned using ultrasonic cleaning equipment to remove impurities from the surface of the carbon fiber material. During the ultrasonic cleaning process, it is necessary to ensure that the structural integrity of the carbon fiber is not affected. In step S102, the aim is to remove the water stains remaining during the cleaning process of the carbon fiber material. In the specific drying process, the cleaned carbon fiber material is placed in a vacuum oven at a drying temperature of 75°C for 10 hours until the fiber material is completely dry and there is no solvent or moisture residue. The moisture content S (%) can be calculated using the following formula: ; Where N1 is the mass of the fiber material before drying, and N2 is the mass of the fiber material after drying, with S ≤ 0.1% required; In step S103, the surface of the carbon fiber material is activated to improve its surface activity. Specifically, the surface of the carbon fiber material is activated by a plasma treatment device to increase the surface roughness and active sites. The plasma treatment device has a power of 300 watts and a treatment time of 8 minutes.

[0023] Step S2 specifically includes preparing a polyimide precursor solution and adding other functional fillers thereto to optimize the sizing performance, specifically including the following steps: S201, dissolving resin; S202, with added thermally conductive filler; S203, dilution adjustment; In step S201, specifically, polyimide powder is taken and an appropriate amount of solvent is added. The solvent can be N-methylpyrrolidone or N,N-dimethylacetamide. The powder is fully dissolved until a stable solution with a solid content of 12% is obtained. During the dissolution process, mechanical stirring is used to assist the dissolution until a uniform and transparent liquid solution is formed. The solid content G (%) is calculated using the following formula: ; Where g1 is the mass of resin and g2 is the mass of solvent; In step S202, thermal conductivity is enhanced by adding thermally conductive filler, which is spherical alumina Al2O3. The amount of thermally conductive filler added is controlled at 10%. The thermally conductive filler is uniformly dispersed in the matrix by ball milling. In step S203, the amount of solvent is adjusted according to the required viscosity until the viscosity is adjusted to 3000 mPa•s at 25°C to meet the coating requirements; Excessive viscosity can lead to uneven resin adhesion during coating, while excessively low viscosity can affect the stability of the coating. Therefore, it is necessary to flexibly control the viscosity to ensure fiber wettability and coating uniformity. In the process of controlling viscosity, the viscosity is measured by a rotational viscometer. When the viscosity is insufficient, i.e., viscosity <2000 mPa•s, the resin ratio can be increased. When the viscosity is too high, i.e., viscosity >5000 mPa•s, solvent can be added for dilution.

[0024] Step S3 involves uniformly coating and depositing the prepared polyimide resin sizing solution onto the surface of the carbon fiber material. Specifically, a superimposed sizing process combining spraying and impregnation is used to achieve sizing. The spraying equipment involved in the spraying method and the sizing tank involved in the impregnation method are integrated and connected to form a single-channel sizing process line. During the sizing process, the carbon fiber material is moved by a traction device. When the carbon fiber material passes through the spraying equipment, the sizing liquid is atomized into fine droplets by the atomizing device and evenly sprayed onto the surface of the carbon fiber material. During the spraying process, it is necessary to control the spraying pressure and spraying spacing. The spraying pressure is controlled at 0.3MPa, and the spraying spacing refers to the distance between the nozzle and the carbon fiber material. The spraying spacing is 14cm to achieve sizing by spraying. After the carbon fiber material is fully sprayed by the spraying equipment, the traction equipment pulls the carbon fiber material to continue moving to the sizing tank. During the process of the traction equipment pulling the carbon fiber material, the sprayed carbon fiber material is slightly shaken, so that the sizing liquid adsorbed by the spraying can fully penetrate into the carbon fiber material. Meanwhile, under the traction of the traction equipment, the carbon fiber material after spraying will be slowly pulled to the sizing tank and stably passed through the sizing tank to achieve sizing. During the sizing process, it is necessary to control the moving speed between the carbon fiber material and the sizing tank, and at the same time control the residence time of the carbon fiber material in the sizing tank. The moving speed is 2m / min and the residence time is 12 seconds. The immersion time T (seconds) is calculated using the following formula: ; Where k1 is an empirical constant, and its range is: n is the number of bundles (strands / M), η is the viscosity of the sizing solution, ranging from 2000 to 5000 mPa•s, and d is the diameter of the fiber material, ranging from 5 to 15 μm.

[0025] Step S3: After the carbon fiber material passes through the sizing tank, the moisture content of the sizing film layer of the carbon fiber material needs to be precisely controlled by the extrusion roller. The moisture content needs to be controlled between 20-40% to ensure that the carbon fiber material is completely impregnated and there are no air bubbles left. The moisture content M (%) is calculated using the following formula: ; Where m1 is the weight of the fiber material after impregnation, and m2 is the weight of the fiber material after pretreatment and drying.

[0026] Step S4 involves a curing process to fully convert the polyimide resin into a stable polymer structure. This curing process includes the following steps: S401, preliminary drying treatment; S402, multi-step stepped curing treatment; In step S401, the carbon fiber material after sizing is transferred to a hot air oven for preliminary drying. The drying temperature of the hot air oven is controlled at 90°C and the drying time is set to 8 minutes to allow some of the solvent inside the carbon fiber material to evaporate, while avoiding solvent loss or thinning of the coating layer due to solvent vaporization. In step S402, the multi-step stepped curing process includes two stages: a first curing stage and a second curing stage. The time and temperature of the two curing stages need to be adjusted accordingly based on the selected steps. In the first curing stage: the carbon fiber material after preliminary drying is placed in a constant temperature oven at 130℃ for 2 hours to complete the subsequent oligomerization reaction and form a partially cross-linked structure, thus avoiding defects and unevenness in the matrix structure. In the second curing stage: the carbon fiber material cured in the first fixing stage is placed in a high-temperature oven at 290℃ for 1 hour to complete the high-temperature cross-linking polymerization of the matrix, form a three-dimensional network structure, and improve the thermal stability of the material. In the initial drying stage, the first curing stage, and the second curing stage of carbon fiber materials, at the end of each stage, the carbon fiber materials need to be allowed to cool naturally to room temperature to ensure the curing effect of each stage. In the second curing stage, the temperature needs to be kept stable to prevent excessively high local temperatures from causing degradation or oxidation reactions.

[0027] Step S4: After the carbon fiber material is processed and cured, the surface of the carbon fiber material needs to be optimized. The specific optimization methods include surface trimming and annealing. During surface finishing, an electrostatic elimination device is used to reduce electrostatic adsorption and prevent fiber aggregation caused by static electricity. At the same time, a light roller pressing method is used to improve fiber bundle properties and ensure uniform and gentle contact between fibers. During annealing, the material is treated at 250°C for 1 hour in a nitrogen-protected environment to release the internal stress generated during curing and increase the stability of the interfacial bonding. After annealing, the fiber material is cooled to room temperature.

[0028] Step S5 involves the sizing and curing process of the fiber material, including the impregnation time, curing temperature, fiber diameter, and number of bundles. The optimization of the impregnation time aims to ensure uniform penetration of the sizing solution without bubbles, while the optimization of the curing temperature aims to maximize the degree of resin crosslinking and interfacial bonding. The impregnation time and curing temperature need to be adjusted according to the fiber diameter and the number of bundles. The optimal parameter combination is determined by adjustment. Specifically, this includes analyzing the relationship between impregnation time and fiber diameter and the number of bundles, and analyzing the relationship between curing temperature and fiber diameter and the number of bundles. When analyzing the relationship between impregnation time and fiber diameter and bundle number, the impregnation time directly affects the penetration depth and adsorption uniformity of the sizing solution on the carbon fiber surface. Fiber diameter and bundle number affect the impregnation time through the following mechanisms, where fiber diameter is divided into fine fibers and coarse fibers, and bundle number is divided into high bundle number and low bundle number: Fine fibers have a large specific surface area, so the sizing solution is absorbed faster, but the pores are smaller and the permeation resistance is greater. Coarse fibers have a small specific surface area, so the absorption is slower, but the permeation resistance is smaller. Therefore, the impregnation time is negatively correlated with the fiber diameter. As the fiber diameter increases, the impregnation time decreases. A high bundle number means that more monofilaments are tightly packed, with the inner fibers being wrapped by the outer fibers. The sizing solution needs a longer time to penetrate into the bundle. A low bundle number means that the fibers are dispersed and penetration is easier. Therefore, the impregnation time is positively correlated with the bundle number. As the bundle number increases, the impregnation time is extended. When analyzing the relationship between curing temperature and fiber diameter and bundle number, the curing temperature affects the crosslinking reaction rate and extent of polyimide resin. Fiber parameters influence temperature selection through the following mechanisms: Fine fibers have a large specific surface area, short resin diffusion paths, and fast reaction rates, requiring lower temperatures to avoid over-curing. Coarse fibers have long diffusion paths and slow reaction rates, requiring appropriate temperature increases to promote cross-linking. Therefore, curing temperature is negatively correlated with fiber diameter; as fiber diameter increases, temperature decreases. High-bundle-count fiber bundles have more internal voids, requiring a longer resin diffusion time and necessitating higher temperatures to accelerate the reaction. Low-bundle-count fibers are more dispersed, resulting in a more uniform reaction and allowing for lower temperatures. Therefore, curing temperature is positively correlated with the bundle number; as the bundle number increases, the temperature rises.

[0029] Step S5: Using fiber diameter and bundle number as control factors, and impregnation time and curing temperature as response variables, optimize impregnation time and curing temperature respectively. During the optimization of impregnation time, the fiber diameter was 3μm, the number of bundles was 1K, and other process parameters were kept constant. The impregnation time was adjusted in 1s increments within the range of 5-10s. The amount of sizing was measured. If the amount of sizing was less than the target amount of sizing, the impregnation time needed to be extended. If the amount of sizing was greater than the target amount of sizing or air bubbles appeared, the impregnation time needed to be shortened in order to determine the optimal impregnation time. During the curing temperature optimization process, the first stage temperature is 120-150℃, and the second stage temperature is 280-300℃. The temperature is adjusted in increments of 10℃ within the temperature range. The performance after curing is tested. The higher the curing temperature, the better the degree of crosslinking, the higher the shear strength, and the stronger the interfacial bonding force, so as to determine the final optimal first stage temperature and second stage temperature. Specifically, when the fiber diameter is 3μm and the number of bundles is 1K, the temperature of the first stage is 130℃ and the temperature of the second stage is 290℃. When the fiber diameter is 7μm and the number of bundles is 12K, the temperature of the first stage is 145℃ and the temperature of the second stage is 300℃.

[0030] Step S6, the performance testing of the fiber material, involves a comprehensive performance evaluation of the sized fiber material to ensure that it meets actual production requirements. The specific performance testing process includes the following steps: S601, thermal conductivity test; S602, Shear performance test; In step S601, the thermal conductivity test is performed by measuring the axial thermal conductivity of the fiber material using a laser flare method. The standard target value should be ≥10 W / (m•K) to verify the thermal conductivity required for fiber reinforcement. The material's thermal conductivity k needs to be calculated using the thermal diffusivity α, specific heat capacity Cp, and density ρ, specifically using the following formula: ; Where α is the thermal diffusivity (m² / s), Cp is the specific heat capacity at constant pressure (J / (kg•K)), and ρ is the density (kg / m³). During the thermal conductivity test, it is necessary to repeat the measurement multiple times in a standard high thermal conductivity environment to ensure the accuracy and reliability of the data; In step S602, the shear performance test is to test the interfacial shear strength of the fiber material. The interfacial bonding force between polyimide and carbon fiber is evaluated by using a single fiber pull-out test, and the peel strength value needs to be paid attention to. When testing the interfacial shear strength of fiber materials, the interfacial shear strength I is calculated through a single fiber pull-out experiment: ; Where fm is the maximum pull-out force (N) and A is the contact area between the fiber and the matrix (m²). Typically, a peel strength value greater than 40 MPa is required to verify the comprehensive mechanical properties of the material after matrix reinforcement. The combined sizing process using spraying and dipping methods was compared with the traditional sizing process using only spraying and dipping methods. The results are shown in the table below:

[0031] As can be seen from the table above, the spraying method is simple, but its uniformity and adhesion are insufficient, making it suitable for low-precision applications. The immersion method has better uniformity than the spraying method and is less expensive, but it has reduced bubble residue and penetration limitation. The sizing process of spraying + immersion can combine the advantages of pre-wetting in spraying and deep penetration in immersion, resulting in optimal uniformity, bubble control, and interfacial adhesion, and significantly improved overall performance.

[0032] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for sizing high thermal conductivity mesophase pitch-based carbon fibers with polyimide resin, characterized in that: Includes the following steps: Step S1, Pre-treatment of the fiber material surface; Step S2: Prepare the polyimide resin sizing solution; Step S3: Apply a sizing process to the surface of the fiber material; Step S4: Multi-stage curing treatment of fiber materials; Step S5: Perform an impact analysis on the process parameters; Step S6: Post-performance testing of fiber materials.

2. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 1, characterized in that: Step S1 involves pretreating the highly thermally conductive mesophase pitch-based carbon fiber to enhance the wettability of the fiber material surface and its interfacial bonding force with the resin slurry. Before pretreating the fiber material, it is necessary to determine the fiber diameter and bundle number. The specific pretreating methods include the following steps: S101, Cleaning treatment; S102, drying treatment; S103, surface activated; In step S101, the aim is to remove contaminants adsorbed on the surface of the carbon fiber material, improve the cleanliness of the carbon fiber material surface, and facilitate better subsequent sizing. In the specific cleaning process, organic solvents are used in combination with ultrasonic cleaning equipment to perform ultrasonic cleaning treatment on the mesophase pitch-based carbon fiber material to remove impurities on the surface of the carbon fiber material. During the ultrasonic cleaning process, it is necessary to ensure that the structural integrity of the carbon fiber is not affected. In step S102, the aim is to remove the water stains remaining during the cleaning process of the carbon fiber material. In the specific drying process, the cleaned carbon fiber material is placed in a vacuum oven at a drying temperature of 60-80°C for 8-12 hours until the fiber material is completely dry and there is no solvent or moisture residue. In step S103, the surface of the carbon fiber material is activated to improve its surface activity. Specifically, the surface of the carbon fiber material is activated by a plasma treatment device to increase the surface roughness and active sites. The power of the plasma treatment device is 200-400 watts, and the treatment time is 4-10 minutes.

3. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 1, characterized in that: Step S2 specifically includes preparing a polyimide precursor solution and adding other functional fillers thereto to optimize the sizing performance, specifically including the following steps: S201, dissolving resin; S202, with added thermally conductive filler; S203, dilution adjustment; In step S201, specifically, polyimide powder is taken, an appropriate amount of solvent is added, and it is fully dissolved until a stable solution with a solid content of 10-20% is obtained. During the dissolution process, mechanical stirring is used to assist the dissolution until a uniform and transparent liquid solution is formed. In step S202, thermal conductivity is enhanced by adding thermally conductive filler. The amount of thermally conductive filler added is controlled at 5-15%. The thermally conductive filler is uniformly dispersed in the matrix by ball milling. In step S203, the amount of solvent is adjusted according to the required viscosity until the viscosity is adjusted to 2000-5000 mPa•s at 25°C to meet the coating requirements. Excessive viscosity can lead to uneven resin adhesion during coating, while excessively low viscosity can affect the stability of the coating. Therefore, it is necessary to flexibly control the viscosity to ensure fiber wettability and coating uniformity. In the process of controlling viscosity, the viscosity is measured by a rotational viscometer. When the viscosity is insufficient, i.e., viscosity <2000 mPa•s, the resin ratio can be increased. When the viscosity is too high, i.e., viscosity >5000 mPa•s, solvent can be added for dilution.

4. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 1, characterized in that: Step S3 involves uniformly coating and depositing the prepared polyimide resin sizing solution onto the surface of the carbon fiber material. Specifically, a superimposed sizing process combining spraying and impregnation is used to achieve sizing. The spraying equipment involved in the spraying method and the sizing tank involved in the impregnation method are integrated and connected to form a single-channel sizing process line. During the sizing process, the carbon fiber material is moved by a traction device. As the carbon fiber material passes through the spraying equipment, the sizing liquid is atomized into fine droplets and evenly sprayed onto the surface of the carbon fiber material using an atomizing device. During the spraying process, it is necessary to control the spraying pressure and spraying spacing. The spraying pressure is controlled at 0.2-0.5MPa, and the spraying spacing refers to the distance between the nozzle and the carbon fiber material. The spraying spacing is 10-20cm to achieve sizing by spraying. After the carbon fiber material is fully sprayed by the spraying equipment, the traction equipment pulls the carbon fiber material to continue moving to the sizing tank. During the process of the traction equipment pulling the carbon fiber material, the sprayed carbon fiber material is slightly shaken, so that the sizing liquid adsorbed by the spraying can fully penetrate into the carbon fiber material. Meanwhile, under the traction of the traction equipment, the carbon fiber material after spraying will be slowly pulled to the sizing tank and stably passed through the sizing tank to achieve sizing. During the sizing process, it is necessary to control the moving speed between the carbon fiber material and the sizing tank, and at the same time control the residence time of the carbon fiber material in the sizing tank. The moving speed is 1-3m / min and the residence time is 10-20 seconds.

5. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 4, characterized in that: In step S3, after the carbon fiber material passes through the sizing tank, the moisture content of the sizing film layer of the carbon fiber material needs to be precisely controlled by the extrusion roller. The moisture content needs to be controlled between 20-40% to ensure that the carbon fiber material is completely impregnated and there are no air bubbles left.

6. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 1, characterized in that: Step S4 involves a curing process that allows the polyimide resin to be fully converted into a stable polymer structure. This curing process specifically includes the following steps: S401, preliminary drying treatment; S402, multi-step stepped curing treatment; In step S401, the carbon fiber material after sizing is transferred to a hot air oven for preliminary drying. The drying temperature of the hot air oven is controlled at 80-100℃ and the drying time is set to 5-10 minutes to allow some of the solvent inside the carbon fiber material to evaporate, while avoiding solvent loss or thinning of the coating layer due to solvent vaporization. In step S402, the multi-step stepped curing process includes two stages: a first curing stage and a second curing stage. The time and temperature of the two curing stages need to be adjusted accordingly based on the selected steps. In the first curing stage: the carbon fiber material after preliminary drying is placed in a constant temperature oven at 120-150℃ for 2-3 hours to complete the subsequent oligomerization reaction, form a partially cross-linked structure, and avoid matrix structure defects and unevenness. In the second curing stage: the carbon fiber material cured in the first fixing stage is placed in a high-temperature oven at 280-300℃ for 1-2 hours to complete the high-temperature cross-linking polymerization of the matrix, form a three-dimensional network structure, and improve the thermal stability of the material. In the initial drying stage, the first curing stage, and the second curing stage of carbon fiber materials, at the end of each stage, the carbon fiber materials need to be allowed to cool naturally to room temperature to ensure the curing effect of each stage. In the second curing stage, the temperature needs to be kept stable to prevent excessively high local temperatures from causing degradation or oxidation reactions.

7. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 6, characterized in that: In step S4, after the carbon fiber material is processed and cured, the surface of the carbon fiber material needs to be optimized. The specific optimization methods include surface trimming and annealing. During surface finishing, an electrostatic elimination device is used to reduce electrostatic adsorption and prevent fiber aggregation caused by static electricity. At the same time, a light roller pressing method is used to improve fiber bundle properties and ensure uniform and gentle contact between fibers. During annealing, the material is treated at 250°C for 1 hour in a nitrogen-protected environment to release the internal stress generated during curing and increase the stability of the interfacial bonding. After annealing, the fiber material is cooled to room temperature.

8. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 1, characterized in that: Step S5 involves the sizing and curing processes of the fiber material. The process parameters involved include impregnation time, curing temperature, fiber diameter, and number of bundles. Optimization of the impregnation time aims to ensure uniform penetration of the sizing solution without bubbles, while optimization of the curing temperature aims to maximize the degree of resin crosslinking and interfacial bonding. The impregnation time and curing temperature need to be adjusted according to the fiber diameter and the number of bundles. The optimal parameter combination is determined by adjustment. Specifically, this includes analyzing the relationship between impregnation time and fiber diameter and the number of bundles, and analyzing the relationship between curing temperature and fiber diameter and the number of bundles. When analyzing the relationship between impregnation time and fiber diameter and bundle number, the impregnation time directly affects the penetration depth and adsorption uniformity of the sizing solution on the carbon fiber surface. Fiber diameter and bundle number affect the impregnation time through the following mechanisms, where fiber diameter is divided into fine fibers and coarse fibers, and bundle number is divided into high bundle number and low bundle number: Fine fibers have a large specific surface area, so the sizing solution is absorbed faster, but the pores are smaller and the permeation resistance is greater. Coarse fibers have a small specific surface area, so the absorption is slower, but the permeation resistance is smaller. Therefore, the impregnation time is negatively correlated with the fiber diameter. As the fiber diameter increases, the impregnation time decreases. A high bundle number means that more monofilaments are tightly packed, with the inner fibers being wrapped by the outer fibers. The sizing solution needs a longer time to penetrate into the bundle. A low bundle number means that the fibers are dispersed and penetration is easier. Therefore, the impregnation time is positively correlated with the bundle number. As the bundle number increases, the impregnation time is extended. When analyzing the relationship between curing temperature and fiber diameter and bundle number, the curing temperature affects the crosslinking reaction rate and extent of polyimide resin. Fiber parameters influence temperature selection through the following mechanisms: Fine fibers have a large specific surface area, short resin diffusion paths, and fast reaction rates, requiring lower temperatures to avoid over-curing. Coarse fibers have long diffusion paths and slow reaction rates, requiring appropriate temperature increases to promote cross-linking. Therefore, curing temperature is negatively correlated with fiber diameter; as fiber diameter increases, temperature decreases. High-bundle-count fiber bundles have more internal voids, requiring a longer resin diffusion time and necessitating higher temperatures to accelerate the reaction. Low-bundle-count fibers are more dispersed, resulting in a more uniform reaction and allowing for lower temperatures. Therefore, curing temperature is positively correlated with the bundle number; as the bundle number increases, the temperature rises.

9. The polyimide resin sizing method for high thermal conductivity mesophase pitch-based carbon fibers according to claim 8, characterized in that: In step S5, the impregnation time and curing temperature are optimized, with fiber diameter and bundle number as control factors and impregnation time and curing temperature as response variables, respectively. During the optimization of impregnation time, the fiber diameter was 3μm, the number of bundles was 1K, and other process parameters were kept constant. The impregnation time was adjusted in 1s increments within the range of 5-10s. The amount of sizing was measured. If the amount of sizing was less than the target amount of sizing, the impregnation time needed to be extended. If the amount of sizing was greater than the target amount of sizing or air bubbles appeared, the impregnation time needed to be shortened in order to determine the optimal impregnation time. During the curing temperature optimization process, the first stage temperature was 120-150℃, and the second stage temperature was 280-300℃. The temperature was adjusted in increments of 10℃ within the temperature range, and the performance after curing was tested. The higher the curing temperature, the better the degree of crosslinking, the higher the shear strength, and the stronger the interfacial bonding force, so as to determine the final optimal first stage temperature and second stage temperature.

10. The method for sizing high thermal conductivity mesophase pitch-based carbon fibers with polyimide resin according to claim 1, characterized in that: Step S6, the performance testing of the fiber material, is a comprehensive performance evaluation of the sized fiber material to ensure that it meets actual production requirements. The specific performance testing process includes the following steps: S601, thermal conductivity test; S602, Shear performance test; In step S601, the thermal conductivity test is performed by measuring the axial thermal conductivity of the fiber material using the laser flare method. The standard target value should be ≥10W / (m•K) to verify the thermal conductivity required for fiber reinforcement. During the thermal conductivity test, it is necessary to repeat the measurement multiple times in a standard high thermal conductivity environment to ensure the accuracy and reliability of the data; In step S602, the shear performance test is to test the interfacial shear strength of the fiber material. The interfacial bonding force between polyimide and carbon fiber is evaluated by using a single fiber pull-out test, and the peel strength value needs to be paid attention to. Typically, a peel strength value greater than 40 MPa is expected to be required to verify the overall mechanical properties of the material after matrix reinforcement.

Citation Information

Cited By

  • A highly conductive pitch-based carbon fiber prepreg and its preparation method

    CN122404770A